2018
DOI: 10.1186/s41100-018-0193-4
|View full text |Cite
|
Sign up to set email alerts
|

Glecaprevir and pibrentasvir combination therapy for hepatitis C virus-infected Japanese patients on hemodialysis

Abstract: Background: It remains unclear whether hepatitis C virus (HCV)-infected Japanese patients on hemodialysis (HD) have an altered viral response to glecaprevir (GLE) and pibrentasvir (PIB) combination therapy and whether this treatment is safe for this patient group. Therefore, we investigated the characteristics associated with virological response to GLE and PIB combination therapy for HCV in Japanese patients undergoing HD. This study aimed to evaluate the safety and efficacy of GLE and PIB combination therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…We observed that HD patients demonstrated good GLE/PIB therapy tolerance. Adverse effects in our group were only skinrelated (itching) in a small proportion of patients, which is fully consistent with the data provided by Hotta N & Tanaka Y et al [19,20]. There were no cases of the early termination of the antiviral therapy.…”
Section: Advanced Research In Gastroenterology and Hepatologysupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that HD patients demonstrated good GLE/PIB therapy tolerance. Adverse effects in our group were only skinrelated (itching) in a small proportion of patients, which is fully consistent with the data provided by Hotta N & Tanaka Y et al [19,20]. There were no cases of the early termination of the antiviral therapy.…”
Section: Advanced Research In Gastroenterology and Hepatologysupporting
confidence: 92%
“…In three other Japanese studies, HD patients with genotypes 1 and 2 were treated with this combination for 8 or 12 weeks, with the duration of the treatment determined by the cirrhosis status. According to Kumada H et al [18] and Hotta N [19], SVR12 was 100% as was in our HD patients' group, while Tanaka Y [20] reported a SVR12 rate of 94.4%. There is a lack of data related to HCV treatment in 2k/1b-infected patients, especially with modern DAA therapy.…”
Section: Discussionsupporting
confidence: 54%
“…However, patients with end-stage renal disease or who are undergoing haemodialysis can be successfully treated with glecaprevir/pibrentasvir, although some patients may experience pruritus. [32][33][34][35]…”
Section: Current Tre Atmentsmentioning
confidence: 99%
“…Furthermore, patients who underwent prior hepatitis C treatment, received a liver transplant, had known or suspected hepatocellular carcinoma (HCC), are positive for HIV or HBsAg, or who have experience decompensated cirrhosis may not be eligible for this simplified treatment. However, patients with end‐stage renal disease or who are undergoing haemodialysis can be successfully treated with glecaprevir/pibrentasvir, although some patients may experience pruritus 32‐35 …”
Section: Current Treatmentsmentioning
confidence: 99%